2016
DOI: 10.1002/cncr.29903
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐one–gene recurrence score assay in BRCA‐associated versus sporadic breast cancers: Differences based on germline mutation status

Abstract: BACKGROUND: Biological differences between BRCA-associated breast cancer and sporadic breast cancer may warrant different adjuvant chemotherapy (ACRx) recommendations despite similar phenotypic features. A 21-gene expression profile (Oncotype DX) generates a prognostic recurrence score (RS) that predicts the ACRx benefit in patients with hormone receptor-positive breast cancer. No reports describe assay results for BRCA-associated breast cancer. METHODS: A review of Memorial Sloan Kettering Cancer Center datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 23 publications
4
35
0
6
Order By: Relevance
“…McAndrew et al . reported similar RS distribution among carriers and noncarriers while our series and the other two BRCA populations exhibited significantly higher RS among carriers compared with controls. We combined our data with the RS distribution found in these three studies to enlarge BRCA population for comparison.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…McAndrew et al . reported similar RS distribution among carriers and noncarriers while our series and the other two BRCA populations exhibited significantly higher RS among carriers compared with controls. We combined our data with the RS distribution found in these three studies to enlarge BRCA population for comparison.…”
Section: Resultssupporting
confidence: 79%
“…The Oncotype Dx RS distribution of our carrier group and that of three previous studies compared with the general BC population are presented in Table . McAndrew et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Bayraktar et al [27] observed that overall prognosis of TN breast cancer in BRCA carriers and non-carriers was not significantly different within the first 5 years following initial diagnosis. In contrast, the aggressive nature of these breast cancers has been demonstrated through a higher median Oncotype DX recurrence score in ER-positive, node negative BRCA-associated breast cancers as compared with controls [28] and an inferior overall survival (OS) in BRCA1 mutation carriers with breast and ovarian cancer as compared with non-carrier patients. Notably, this OS difference was not seen in BRCA2 mutation carriers [29].…”
Section: Genetic Testing For Hereditary Breast and Ovarian Cancer Synmentioning
confidence: 90%
“…The spectrum of breast cancer phenotypes in BRCA2 gene mutation carriers is much more heterogeneous 55,56. Shah et al retrospectively investigated the utility of Oncotype DX in patients with BRCA1 / BRCA2 gene mutations and ER-positive breast cancer 57. Mutation carriers were more likely than age-matched controls to have RS in the intermediate- or high-risk range and overall had higher median RS.…”
Section: Challenging Clinical Scenariosmentioning
confidence: 99%